EVALUASI SISTEM DAN PROSES PENGAJARAN TERHADAP LULUSAN AKPOL 2006 – 2010 DI WILAYAH POLDA NUSA TENGGARA BARAT (NTB) - Cecep Tedi Siswanto; Puguh Windrawan (Universitas Janabadra, 2017)
This assessment is linked to the respondent answers given to the questions given. The question that is open and qualitatively reflect the depth of their thoughts on the situation at hand. Along with the fact that there are some things that concern in it. This is related to internal accountability that is in the body of the local police. Like what is described by M. Adiel Ipda Aristo, Kanit Regident Then Bima City and Ipda Cita gift Sari, Chief of Unit 2 Satreskrim Idik West Lombok Police. Internal issues such as the perception of his colleagues to the position Ipda M. Adiel Aristo, which considers that the position is a